Brain power: the political economy of higher education - Idema, T (2011)
This dissertation disputes conventional interpretations of the comparative political economy literature on higher education. In particular, I challenge the common assumption that access to higher education is structured by income. Instead, based on insights from the relevant psychology, sociology and economics literature, I argue that a child’s probability of entering higher education is predominantly a function of her abilities, and that her abilities are strongly related to her parents’ level of education. I develop a theory of the distributive politics of higher education solidly grounded in this relationship. The result of this model is the counter intuitive hypothesis that the initial expansions of higher education benefit the children of more highly educated parents. Moreover, more highly educated families are the net beneficiaries of free higher education and generous subsidies. Extensive survey evidence from Britain, Australia, Canada and Sweden of higher education policy preferences confirms this picture of the politics of higher education as a zero-sum distributive game between highly and lesser educated families. In order to analyse the consequences of these preference patterns for higher education policy, I develop a theoretical and empirical measure of voting power for multi-party systems. Voting power measures how many votes a party stands to gain from converting and mobilising voters by distributing resources from one group to another. Using data from 15 EU countries, I show that parliaments and cabinets, on average, stand to win more votes from pleasing highly educated voters than from targeting less educated voters. Furthermore, the conversion imperative is much stronger than the mobilisation imperative. Statistical analyses show that variations in the voting power of highly educated individuals over the government help to explain variations in higher education policy across countries and within countries over time. All in all, the theoretical and empirical analyses presented in this dissertation represent a significant contribution towards understanding the specific distributive politics of higher education, and the political economy of redistribution more generally.